Identification of Hydraulic Connection Points between Different Confined Aquifers in the Liyazhuang Coal Mine - Zhenghe Liu; Peiyun Zhao; Lusheng Yang; Jingui Zhao; Hailong Ye; Jun Yang; Rujun Mo (Geofluids)
Water inrush from coal seam floors is one major geological obstacle hindering safe and efficient production activities in mines. Determining the source of water inrush can facilitate its prediction and guide decisions regarding measures for prevention and control. The process of identifying the location of hidden hydraulic contact points in different confined aquifers forms the basis of hydrogeological explorations. It is also the basis for categorizing mine areas prone to water inrush and making qualitative decisions regarding the prevention and control of water inrush. In this study, the positions of hidden hydraulic contact points between the Ordovician Fengfeng and Shangmajiagou formations in the basement of the Liyazhuang coal mine were determined using numerical simulations of the flow fields. First, each node of the finite element grid was considered as a water inrush point to determine the water level at other nodes. Subsequently, the error between measured and simulated water levels, determined based on the flow fields, was determined using the least squares method. The node with the minimum error was then considered as the hidden hydraulic contact point. The simulation results for the flow field indicate a distance of 5000 m between the hydraulic connection and the water inrush points located between the peak formation and the Majiagou aquifer in the Liyazhuang coal mine. Furthermore, the hydraulic relationship between them is poor. Observational data of water inrush from the floor of the No. 2 coal seam and the water level of the confined aquifer in the Liyazhuang coal mine, including the water quality test data of different Ordovician ash aquifers, show that the source of water inrush from the floor of the No. 2 coal seam is the aquifer of the Fengfeng Formation. This finding is consistent with the results of the numerical simulations of the flow field. The results demonstrate that, in mining areas subjected to high pressures, numerical simulations of the flow field can serve as an effective tool for determining the location of hidden hydraulic contact points.